Hindsight Bias in Depression. (September 2017) - Groß, Julia; Blank, Hartmut; Bayen, Ute J.
People tend to be biased by outcome knowledge when looking back on events. This phenomenon is known as hindsight bias. Clinical intuition and theoretical accounts of affect-regulatory functions of hindsight bias suggest a link between hindsight bias and depression, but empirical evidence is scarce. In two experiments, participants with varying levels of depressive symptoms imagined themselves in everyday scenarios that ended positively or negatively and completed hindsight and affect measures. Participants with higher levels of depression judged negative outcomes, but not positive outcomes, as more foreseeable and more inevitable in hindsight. For negative outcomes, they also misremembered prior expectations as more negative than they initially were. This memory hindsight bias was accompanied by disappointment, suggesting a relation to affect-regulatory malfunction. We propose that "depressive hindsight bias" indicates a negative schema of the past and that it sustains negative biases in depression.